2009
DOI: 10.1021/mp900122j
|View full text |Cite
|
Sign up to set email alerts
|

An Imaging-Driven Model for Liposomal Stability and Circulation

Abstract: Simultaneous labeling of the drug compartment and shell of delivery vehicles with optical and positron emission tomography (PET) probes is developed and employed to inform a physiologically-based pharmacokinetic model. Based on time-dependent estimates of the concentration of these tracers within the blood pool, reticulo-endothelial system (RES) and tumor interstitium, we compare the stability and circulation of long-circulating and temperature-sensitive liposomes. We find that rates of transport to the RES fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 38 publications
0
52
0
Order By: Relevance
“…This was accomplished by conjugating a chelating agent, AmBaSar, onto the ELP prior to radiolabeling with 64 Cu. In contrast to the classical method of obtaining blood samples to deduce pharmacokinetics, this imaging modality allows for the application of image-driven pharmacokinetic modeling[83]. These studies confirmed that a low molecular weight soluble ELP (<40 kDa) was cleared rapidly by the kidney, and that high molecular weight soluble ELPs (>70 kDa) were retained in the blood for long enough to generate an EPR-based enhancement in a breast cancer xenograft model.…”
Section: Introductionmentioning
confidence: 73%
“…This was accomplished by conjugating a chelating agent, AmBaSar, onto the ELP prior to radiolabeling with 64 Cu. In contrast to the classical method of obtaining blood samples to deduce pharmacokinetics, this imaging modality allows for the application of image-driven pharmacokinetic modeling[83]. These studies confirmed that a low molecular weight soluble ELP (<40 kDa) was cleared rapidly by the kidney, and that high molecular weight soluble ELPs (>70 kDa) were retained in the blood for long enough to generate an EPR-based enhancement in a breast cancer xenograft model.…”
Section: Introductionmentioning
confidence: 73%
“…is varied over a range of 0.1-10 folds of its baseline value, which is sufficient to cover the parameter values reported in the literature [17,18]. Comparisons of temporal profiles of obtained with the baseline value and the lower and upper bounds are shown in Figure 5(a).…”
Section: Clearance Rate Of Tsl ( )mentioning
confidence: 99%
“…Following administration of a drug encapsulated into drug delivery system, drug disposition is not constant and cannot be described by a single volume of distribution parameter. Pharmacokinetics of drugs incorporated in delivery systems can be described using sophisticated distribution mechanism-based PK models, such as PBPK models [10,55] that can incorporate processes of tissue diffusion and drug release from the delivery system [56,57].…”
Section: Nonlinear Drug Distributionmentioning
confidence: 99%